2015
DOI: 10.1136/bmjopen-2014-006681
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional assessment of the prevalence of multiple chronic conditions and medication use in a sample of community-dwelling adults with fibromyalgia in Olmsted County, Minnesota

Abstract: ObjectivesThe objective of this study was to evaluate the problem of multiple chronic conditions and polypharmacy in patients with fibromyalgia.DesignRetrospective medical record review.SettingOlmsted County, Minnesota.Participants1111 adults with fibromyalgia.Primary and secondary outcome measuresNumber and type of chronic medical and psychiatric conditions, medication use.ResultsMedical record review demonstrated that greater than 50% of the sample had seven or more chronic conditions. Chronic joint pain/deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 18 publications
4
40
0
3
Order By: Relevance
“…It is commonly associated with a variety of comorbidities, including, but not limited to, migraines and sleep difficulties,2,3 and also with mental health conditions, such as anxiety and depression 4. Recently, in Japan, the prevalence of fibromyalgia was estimated to be 2.1% among adults (aged ≥20 years), with the majority (60.5%) of them being female 5…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly associated with a variety of comorbidities, including, but not limited to, migraines and sleep difficulties,2,3 and also with mental health conditions, such as anxiety and depression 4. Recently, in Japan, the prevalence of fibromyalgia was estimated to be 2.1% among adults (aged ≥20 years), with the majority (60.5%) of them being female 5…”
Section: Introductionmentioning
confidence: 99%
“…Drugs for treating NS comorbidities, migraines, dizziness, gastric protectors and the use of analgesics were more common in patients with FM, as described in previous studies [7], but these clinical conditions are also commonly present in many patients without FM.…”
Section: Discussionmentioning
confidence: 78%
“…Separate treatment of clinical manifestations does not guarantee an improvement in the disease and may increase the risk of drug interactions and adverse events adding more clinical manifestations or aggravating them [7]. Some studies have shown that some clinical manifestations such as dizziness—a common symptom in patients with FM—are positively correlated with the number of consumed drugs [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with chronic pain are known to be at increased risk of psychiatric disorders, particularly those involving low mood and anxiety [1][2][3] and Posttraumatic Stress Disorder (PTSD) [4,5]. Evidence shows that chronic pain sufferers with comorbid anxiety, depression, and PTSD present with greater levels of pain-related impairment, respond less well to pain focused treatment, and incur greater health costs [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%